2015
DOI: 10.1177/1045159515573021
|View full text |Cite
|
Sign up to set email alerts
|

From Students to Scholars

Abstract: Participating in a doctoral program can be a transformative experience that shapes the identity of the learner. What learning spaces might best facilitate that identity development? This article presents the findings of a study examining doctoral student perspectives of participating in a Community of Practice (COP) intentionally used to foster emerging scholar identities. The researchers examined the actual experience of the participants, explored the impact on their identities as scholars, and, finally, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…The current need for effective educational leadership preparation is key in ensuring graduates of the program are adequately trained to deal with the increasing complexity of varied administrative roles. Participation in a doctoral program can be a transformative experience that shapes a learner's identity (Kriner, Coffman, Adkisson, Putman, & Monaghan, 2015). When doctoral students do not complete their dissertations, which comes as a great expense to the student, institution, and society, their potential contributions are substantially diminished, which impacts career goals and life plans (Kelley & Salsibury-Glennon, 2015).…”
Section: Educational Leadership Preparation Program Effectivenessmentioning
confidence: 99%
“…The current need for effective educational leadership preparation is key in ensuring graduates of the program are adequately trained to deal with the increasing complexity of varied administrative roles. Participation in a doctoral program can be a transformative experience that shapes a learner's identity (Kriner, Coffman, Adkisson, Putman, & Monaghan, 2015). When doctoral students do not complete their dissertations, which comes as a great expense to the student, institution, and society, their potential contributions are substantially diminished, which impacts career goals and life plans (Kelley & Salsibury-Glennon, 2015).…”
Section: Educational Leadership Preparation Program Effectivenessmentioning
confidence: 99%
“…An abundance of research has investigated the benefits of self-directed learning on student achievement and self-efficacy (Dron & Ostashewski, 2015;Newmann, F. M., Marks, H. M., & Gamoran, A., 1996) Self-directed learning has been shown to enhance learning, problem-solving, and collaborative skills (Kriner, Coffman, Adkisson, Putman, & Monaghan, 2015). Although much of this research has focused on adult learning, some of it has investigated self-directed learning in K-12 settings (Blumenfeld, Marx, Soloway, & Krajcik, 1996;Giannakos, Krogstie, & Aalberg, 2016).…”
Section: Gerald P Ardito Pace Universitymentioning
confidence: 99%
“…Prior research identified potential benefits of video conferencing. Specifically, these studies demonstrated that using video conferencing leads to reduced isolation (Bennett & Folley, 2014), improved engagement (Borup et al, 2012;Kriner, Coffman, Adkisson, Putman, & Monaghan, 2015), and increased persistence (Maor, Ensor, & Fraser, 2015) in graduate students.…”
Section: Selection Of Zoom For Dissertation Coaching and Th Is Studymentioning
confidence: 99%